The Metabolomic Rationale for Treating Perimenopausal Syndrome as Kidney Deficiency. (10th December 2020) - Chen, Xueqin; Wu, Caiming; Liang, Wen'na; Shen, Jianying; Zhuo, Zewei; Hu, Liu; Ruan, Luwei; Zhang, Pengheng; Xu, Leqin; Li, Chengfu; Lin, Shengyuan; Lan, Junjie; et al.
Abstract : Background . Traditional Chinese medicine (TCM) typically attributes the etiopathogenesis of perimenopausal syndrome (PMS) to kidney deficiency in the TCM stratification system for diagnosis. However, the molecular basis of this classical attribution remains to be investigated. Aim of the Study . By unraveling the responses to TCM treatment for kidney deficiency, the metabolomic link between PMS and kidney deficiency can be evaluated for in-depth understanding of the mechanism of TCM treatment and development of better treatment protocols. Materials and Methods . With naturally aged rats as a model for PMS, the metabolomic response to TCM treatment for kidney deficiency was investigated by 1 H NMR. Results . 1 H NMR metabolomic evidence of plasma samples demonstrates that treatments with two classical TCM prescriptions for kidney deficiency, decoctions of Yougui and Zuogui, result in modulating the metabolic state of the disease model towards that of rats of younger age. Conclusion . The data support the notion that kidney deficiency is responsible, in part at least, for PMS, and the relevant prescriptions are helpful in dampening the changes in the body's metabolic states to alleviate symptoms of the disorder.